The influence of limb alignment and transfemoral amputation technique on muscle capacity during gait. Issue 11 (18th August 2017) - Ranz, Ellyn C.; Wilken, Jason M.; Gajewski, Donald A.; Neptune, Richard R.
Abstract: Many factors influence successful outcomes following transfemoral amputation. One factor is surgical technique. In this study, the influence of limb alignment and surgical technique on a muscle's capacity to generate force was examined using musculoskeletal modeling. Non-amputee and transfemoral amputee models were analyzed while hip adduction, femur length, and reattached muscle wrap position, tension and stabilization technique were systematically varied. With muscle tension preserved, wrap position and femur length had little influence on muscle capacity. However, limb alignment, muscle tension and stabilization technique notably influenced muscle capacity. Overall, myodesis stabilization provided greater muscle balance and function than myoplasty stabilization.